Long-term mortality predictors in pulmonary embolism. (26th April 2021) - Caldeira Da Rocha, R; Fernandes, R; Carrington, M; Claudio, F; Pais, J; Trinca, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Acute Pulmonary embolism(PE)is a common and potentially fatal medical condition.In contemporary adult population, PE is associated with increased long-term mortality. Purpose: Identify predictors of long-term all-cause mortality in patients(pts)admitted due to pulmonary embolism. Methods: Retrospective single-center study of hospitalized pts with acute PE between 2015 and 2018.We evaluated comorbidities, admission(AD)presentation such as vitals(with hypotension defined as systolic blood pressure(SBP)<90mmHg, and tachycardia as >100ppm), lab analyses during in-hospital period, imaging features. Mortality(long-term >3months)was also assessed using national registry of citizens.We performed uni and multivariate analysis to compare clinical characteristics of pts who died and who survived, using Cox regression and Kaplan-Meier methods.For the predictor age we assessed discrimination power and defined the best cut-off using area under the ROC curve(AUC)method. Results: From 2015 to 2018, 182 pts were admitted with diagnosis of pulmonary embolism, 60% female with a mean age of 74 ± 13years old.Seventy-one(39%)pts died after a median follow-up of 26[10-41]months.Pts who died were older(80 ± 8 vs71 ± 14, p < 0.001).The best cut-off value of age to predict mortality with 70%sensitivity and 61%specificity was 77years old(AUC 0.703;CI95% 0.63-0.78).Pts who died had more frequently history of neoplasia (21%vs 9%, p = 0.009).The remaining comorbidities were similar in both groups.Pts who did not survive were more frequently hypotensive(28% vs 13%, p = 0.008), had higher creatinine(1.1[0.8-1.4] vs 1.0[0.8-1.2], p = 0.002), lactate(2.3[1.8-2.8]vs 1.8[1.5-2.0], p = 0.007)and NT-proBNP(4694[1498-12300]vs2070[492-6660], p < 0.001)at AD.Maximum troponin I (0.176[0.037-0.727]vs0.126[0.050-0.365]ng/mL, p = 0.012) was also higher than in pts who survived. After adjusting for history of neoplasia, ADcreatinine and maximum troponin I, we found that age (HR1.057;95%CI 1.01-1.11, p = 0.021), AD SBP < 90(HR 2.215;95%CI 1.03-4.76, p = 0.041), lactate(HR 1.17;95%CI 1.01-1.36, p = 0.035)and NT-proBNP(HR 1.510;95%CI 1.250-1.780, p < 0.001)were independent predictors of all-cause mortality. Conclusion: In our cohort, the long-term all-cause mortality was 39%over a median  follow-up of 26[10-41]months.In patients with pulmonary embolism, aside from already identified age(especially when ≥70 years old)and NT-proBNP, lactate should also be considered when evaluating long-term prognosis. Furthermore, hypotension at admission increases by 2fold long-term mortality in patients who suffered acute PE.